2020
DOI: 10.1038/s41467-020-16437-9
|View full text |Cite
|
Sign up to set email alerts
|

Ptychography retrieval of fully polarized holograms from geometric-phase metasurfaces

Abstract: Controlling light properties with diffractive planar elements requires full-polarization channels and accurate reconstruction of optical signal for real applications. Here, we present a general method that enables wavefront shaping with arbitrary output polarization by encoding both phase and polarization information into pixelated metasurfaces. We apply this concept to convert an input plane wave with linear polarization to a holographic image with arbitrary spatial output polarization. A vectorial ptychograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 34 publications
0
121
0
Order By: Relevance
“…Meanwhile, vectorial holpgraphy can also be realized by utilizing phase-only metasurfaces [75] or geometric-phase metasurfacces [76]. Equivalent electromagnetic model and gradient-based nonlinear optimization are adopted to achieve complete control of the complex amplitude of electromagnetic field in the region of interest based on high efficiency phase-only metasurfaces [75].…”
Section: Polarization-multiplexed Holographymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, vectorial holpgraphy can also be realized by utilizing phase-only metasurfaces [75] or geometric-phase metasurfacces [76]. Equivalent electromagnetic model and gradient-based nonlinear optimization are adopted to achieve complete control of the complex amplitude of electromagnetic field in the region of interest based on high efficiency phase-only metasurfaces [75].…”
Section: Polarization-multiplexed Holographymentioning
confidence: 99%
“…And the polarization can also be manipulated freely by tailoring two orthogonal components of fields simultaneously based on subpixel design strategy in order to obtain holographic images with spatially varied polarization states in microwave frequency. Besides, Song et al [76] demonstrated a full-polarization reconstructed metasurface that can produce arbitrary polarization for wavefront shaping under linear polarized light illuminating in broadband by utilizing geometric phase principle. The proposed method relies on pixelated metasurfaces, in which each pixel acts as a deflector able to encode both the polarization and the holographic phase information for reconstructing holographic images with arbitrary polarization at specific angle.…”
Section: Polarization-multiplexed Holographymentioning
confidence: 99%
“…Elliptical birefringence has also been realized with independent phase manipulation based on elliptical eigenpolarization states, leading to arbitrary polarization conversion under a specified input polarization 42 . In addition, combining the geometric phase with the detour phase can allow simultaneous control of the spatially varying arbitrary polarization and phase profiles, leading to powerful vectorial hologram applications 29 , 34 , 43 . However, all of these metasurface polarization optics require an additional polarizer to generate incident beams with well-defined polarization, precluding their applicability in monolithic polarization generators working directly with unpolarized light.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Another method is exploiting the superposition of the two output circular polarization (CP) beams through two sets of nanopillars with different dimensions and starting orientation angles under linear polarization (LP) incidence. [ 28 ] Both of them are based on super unit cells with spatial superposition of inclusions, which would result in lower efficiency, inferior image quality, and lower space‐bandwidth product. Recently, it is of great interest to combine the propagation phase and geometric phase (i.e., Pancharatnam–Berry [PB] phase) to realize full control of the polarization and phase on a single subwavelength unit cell.…”
Section: Introductionmentioning
confidence: 99%